Current trends in e-mental health interventions: Health care providers' attitudes and usage patterns - Elena Caroline Weitzel; Katja Schladitz; Maria Schwenke; Franziska Dinah Welzel; Georg Schomerus; Peter Schönknecht; Markus Bleckwenn; Anja Mehnert-Theuerkauf; Steffi G. Riedel-Heller; Margrit Löbner (Internet Interventions)
Objective: E-mental health interventions can usefully supplement mental health care. Health care providers are important to the routine implementation. Until now, little has been known about their attitudes about e-mental health and its use in treatment. This study aims to comprehensively examine health care providers' attitudes and experiences regarding e-mental health interventions over time. Methods: Data for this explorative analysis derive from a longitudinal study of N = 335 health care providers from four professional groups in German mental health care (GPs, specialist doctors, psychotherapists, and clinicians). In two surveys conducted one year apart, usage as well as advantages of and barriers to e-mental health interventions were assessed. Usage patterns based on self-report were examined according to socio-demographic correlates. In a binary logistic regression, correlations between use at follow-up and baseline variables were analyzed. Results: At follow-up, the inclusion of e-mental health interventions in treatment was increased to 40 % compared to baseline (28.4 %). Also, more participants reported having better knowledge and having received information about e-mental health. Gender, age, and knowledge about e-mental health interventions were significantly associated with usage patterns. In the regression analysis, gender, age, and professional group were relevant predictors of use at follow-up. Conclusion: Our results show that increasingly health care providers are including e-mental health interventions in treatment. This is presumably related to better knowledge. However, it is clear that e-mental health interventions are not yet an established component of health care. Rather, implementation efforts, particularly the dissemination of informational materials, are required to promote the use.